Notary independence in the course of notarial acts - M. Ye. Vasylenko (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of the scientific views of scholars and the norms of current legislation, a list of notarial acts that notaries are authorised to perform has been provided. The author’s own definition of the concept of “notarial acts” has been proposed. The importance of ensuring the independence of notaries in the course of notarial acts has been emphasised. A number of aspects confirming this thesis have been presented.